A Identification of OHS Management System Implementation Using the Fault Tree Analysis Method: Identification of OHS Management System Implementation Using the Fault Tree Analysis Method - Marga Raharja, Adyk; Nusyirwan, Deny (Sustainable, 2023)
Occupational safety and health (OHS) has a protective function to ensure that workers and other people in the workplace are always in a safe state of good health and safety, and that every source of production must be used and operated in a safe and efficient manner. Law No. 1 of 1970 states that regarding safety in the workplace, workers are entitled to protection for their safety. Research at PT Mega Andalan Kalasan has negative findings including Understanding K3 Regulations, Bad smells in the work environment, PPE problems, occupational diseases (PAK), slippery work floors, access to p3k. these findings fall into the moderate to fatal category